Analysis of Shamkh BDiraral-Thubiani`spoem. - Habib, Wahran (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Shamckh `s poem is considered as a model of our old vivid poetry. It is filled with innovation and creation regardless the recurrence of the subjects and some images and meanings . The poet `s journey in life with all it to true and discomfort. It is a Journey whose main aim is persistence and striving. He has started it after he loses all hopes in life. The motifs of the poem resent temporary stage of poetic experience that reveals the suffering of the poet and expresses his aims. The poem seems to have a unified while subject that depicts one controlling idea, which is the motif of work that Shamash believes in to overcome the difficulties. The sensation of hope has over whelmed the poetic text and roamed over the poet `s imagination in his images Meanings ideas and utterances